Poly(vinyl alcohol)-based membranes for metoprolol transdermal delivery. (7th June 2021) - Algieri, C.; Epifanio, A.; Garofalo, A.; Aljlil, S.A.; Donato, L.
ABSTRACT: In this work controlled release devices for transdermal administration of metoprolol were developed. Poly(vinyl alcohol) and poly(vinyl pyrrolidone) were used for producing membranes by solvent-casting technique. The release kinetic of the drug from the membranes was evaluated by ex-vivo experimental studies. All the prepared membranes exhibited a linear release profile in the investigated time. The enhancer Tween 80 was added into the polymeric matrices for improving their performance. Different mathematical models were used for fitting the experimental release data. The model that well described the release mechanism was the zero order, indicating a constant drug release in the time. Graphical Abstract: uf0001